A study of classroom seat (dis)comfort: Relationships between body movements, center of pressure on the seat, and lower limbs' sensations. (January 2019) - Fasulo, Luisa; Naddeo, Alessandro; Cappetti, Nicola
Abstract: The aim of this work is to define a new method that helps researchers to analyze perceptions of (dis)comfort in dynamic conditions. Recent studies pay considerable attention to body movements, mobility, and stability to measure comfort or discomfort when seated. Most of these discuss the relations between subjective comfort/discomfort and objective measurements (e.g. body pressure distribution, body movement and EMG) for short- and medium-term sitting. The present analysis took place in a classroom of the Industrial Engineering Department at the University of Salerno. The participants included 25 students (12 females and 13 males), who were observed during classroom hours. The students were invited to sit at a combo-desk and were free to perform different combinations of movements while writing and listening. These activities required that they adapt their body movements, as the combo-desk was fixed to the floor. A pressure pad was used to detect pressure at interface and center of pressure's changes, allowing for the bodies' motion data to be recorded. The aim was to identify the correct threshold to be used for movement detection and to investigate correlations between the number of movements and the perceived (dis)comfort. The study also identifies those body parts that have the greatest effect on (dis)comfort perception. Highlights: Body movements, pressure at interface and perceived comfort while seated have been investigated. 25 mm is the best threshold for detecting movements through the variation of the center of pressure. School chairs in combo desk have been evaluated in terms of perceived comfort in constrained setup. Perceived (dis)comfort due to movements in constrained posture is different from the perceived (dis)comfort in free posture. The more the duration of the test is long, the more the number of movements is high.